Chronic Hepatitis E is associated with cholangitis - Beer, Andrea (Liver Int, 2019)
BACKGROUND AND AIMS: Sporadic hepatitis E is an emerging indigenous disease in Europe induced by genotype 3 of the virus. While the disease takes an acute self‐limited course in immunocompetent individuals, under immunocompromised conditions chronic hepatitis E might develop. The histology of chronic hepatitis E has not been described in detail systematically. METHODS: Liver biopsies from 19 immunosuppressed patients with chronic hepatitis E were collected: 17 were organ transplant recipients, one had a CD4‐deficiency and one had received steroid therapy because of ulcerative colitis. Biopsies were processed with standard stains. Evaluation of histologic activity and fibrosis was performed according to Ishak. Additionally, immunohistochemistry with antibodies directed against open reading frame 2 and 3 of the virus was performed and liver biopsies were tested for hepatitis E virus RNA. RESULTS: Biochemical data showed an increase in alanine transaminase, aspartate transaminase, gamma‐glutamyl transferase and total bilirubin. Histopathology displayed typical features of chronic hepatitis with mild to moderate activity. The number of polymorphonuclear leucocytes was considerably increased and all patients had a florid cholangitis that presented as a destructive form in five of them. Hepatocytes and bile duct epithelia stained positive for hepatitis E virus by immunohistochemistry. CONCLUSIONS: Chronic hepatitis E in immunocompromised individuals runs a similar course as hepatitis B and C and shows similar histopathology. However, the presence of destructive cholangitis in some cases accompanied by an increased number of polymorphonuclear leucocytes is markedly different. Immunohistochemically the virus is present in bile duct epithelia, seemingly the cause for cholangitis.